Pengabdian Metode Tilawati untuk Peningkatan Kualitas Bacaan Santri di TPQ Al-Ltfilah Nur Desa Situhiang - Muhammad Rijaal Qurrota A'yuni; Fariz Fahmi MR; Agil Laspani; Komalasari (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service program was implemented to address the problem of the low quality of students' Quran reading at TPQ Al-Litfilah Nur, Situhiang Village, which was caused by the lack of implementation of a structured and sustainable tahsin learning method. This activity aims to improve students' Quran reading skills through training and mentoring using the Tilawati method combined with the Asset-Based Community Development (ABCD) approach, so that the potential and resources of the community can be optimized. The program was implemented in stages, including mapping the initial conditions of students' and teachers' abilities, training TPQ teachers on the principles and techniques of the Tilawati method, mentoring the learning process in a classical and individual manner, and evaluating the development of students' reading skills. The results of the activity showed a significant increase in the accuracy of makhraj, the application of basic tajwid, and the fluency of students' Quran reading. In addition, TPQ teachers experienced an increase in pedagogical competence and were able to apply the Tilawati method independently in teaching and learning activities. These findings indicate that strengthening community assets through targeted and participatory training can create meaningful and sustainable changes in improving the quality of Qur'an learning at the TPQ level.